2021
DOI: 10.1016/j.amjsurg.2020.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservation therapy versus mastectomy in the surgical management of invasive lobular carcinoma measuring 4 cm or greater

Abstract: Background: The safety of breast conservation therapy (BCT) has not been demonstrated in large ILC tumors, potentially contributing to the higher mastectomy rates seen in ILC. Methods: We queried a prospectively maintained database to identify patients with ILC measuring 4 cm and evaluated difference in recurrence free survival (RFS) between those treated with BCT versus mastectomy using a multivariate model. Results: Of 180 patients, 30 (16.7%) underwent BCT and 150 (83.3%) underwent mastectomy. Patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As such, these patients may not have been considered good candidates for BCS, since many studies of BCS exclude patients with tumors > 4 cm in size. 27 We chose to evaluate pathologic tumor size, as this would most closely approximate posttreatment tumor size, which is typically the basis for surgical decision making. However, discordance between clinical assessment of posttreatment tumor size and pathologic tumor size in patients with ILC increases the challenge of surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these patients may not have been considered good candidates for BCS, since many studies of BCS exclude patients with tumors > 4 cm in size. 27 We chose to evaluate pathologic tumor size, as this would most closely approximate posttreatment tumor size, which is typically the basis for surgical decision making. However, discordance between clinical assessment of posttreatment tumor size and pathologic tumor size in patients with ILC increases the challenge of surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the present study, Abel et al takes specific aim at ILC tumors measuring 4 cm or greater and finds that while larger tumor size and more advanced nodal stage predict reduced recurrence-free survival (RFS), there were no differences in 5-or 10-year RFS between surgical approaches. 7 The authors conclude that BCS and mastectomy provide similar local control for large ILC tumors.…”
mentioning
confidence: 87%
“…The authors identified no difference in complication rates between BCS and mastectomy in this study, though a re-excision rate of 57% was noted in the BCS group. 7 Similarly, Crown et al found a 51% re-excision rate when performing "extreme oncoplastic" BCS in a cohort of patients traditionally offered mastectomy (multifocal or multicentric tumors and/or disease span 5 cm). 8 With the need for re-excision comes the potential for inadvertent psychological and financial stresses to the patient.…”
mentioning
confidence: 95%
“…It was found that this does not worsen but significantly improves overall survival (OS), [1][2][3][4][5][6][7] even in patients with T3 and T4 tumors. [8][9][10][11][12] Therefore, oncological safety does not prevent the use of BCS in patients with central tumors. Another factor inhibiting the implementation of BCS for central tumors is the technical difficulty of achieving acceptable aesthetic and functional results.…”
Section: Introductionmentioning
confidence: 99%